The effect of biological age in the evaluation of physical indicators and the changes in selected motoric tests of young female basketball players - Doležajová, L.; Gallová, T.; Lednický, A. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2019)
Basketball is a complex team sport, which combines cyclic and acyclic motion structures consisting mainly of fast and dynamic moves with or without a ball. The puberty is characterized by considerable variability that may occur earlier (developmental acceleration, early maturing) or later (developmental retardation, late maturing): an example can be a 12-year-old girl whom biological age could range from 9.5 to 14.5 years. For this study we selected 6 girls-players from the whole team. Two players were according to the norms from the zone of developmental retardation (BioRet), two players whose decimal and biological age i.e. bone age was identical (DC = BV), and the other two were in the biological acceleration zone (BioAkc.). All players were 13-years old and competed in the U14 category. We have confirmed that there are great differences in biological age in a group of 13-years old girls - in our research it has shown almost four years difference. We did not confirm the author's conclusions that biologically accelerated individuals achieved better results than the retarded ones in the speed and strength tests.